Reality versus rhetoric: Assessing the efficacy of third-party hate crime reporting centres - Wong, Kevin (International review of victimology, 2020)
The underreporting of hate crime is recognised as problematic for jurisdictions across Europe and beyond. Within the UK, the landmark inquiry report into the murder of Stephen Lawrence 25 years ago has seen governments faithfully adhering to a policy of promoting the increased reporting of hate crime. An enduring legacy of the inquiry, third-party reporting centres (TPRCs) have been equally faithfully promoted as the primary vehicle for achieving such increases. While the nations of the United Kingdom have pioneered the development of TPRCs, their function and form have been adopted in other jurisdictions, including Victoria, Australia. Nevertheless, despite their reliance on TPRCs, policymakers have given limited attention to their efficacy. The evidence from a plethora of small scale studies has consistently found that TPRCs have been limited by public awareness, capability, capacity and poor oversight difficulties. Responding to these long-standing problems, the authors have developed the first ‘TPRC assessment tool' which offers a diagnostic facility to improve effectiveness. This paper describes the development and piloting of this tool and highlights its potential to inform policy and practice both in the UK and internationally, providing an original contribution to the limited evidence base around third-party reporting.